World development report 1988 : opportunities and risks in managing the world economy - World Bank. (New York : : Oxford University Press, 1988)
Recognized as an indispensable resource for policymakers, economists, journalists, and professionals of all kinds, the World Development Report continues to survey and synthesize contemporary economic issues in developed and developing countries. The 1988 Report surveys opportunities and risks in adjustment and growth worldwide, with a special section on public finance in growth development, providing an up-to-date, informative analysis of recent trends with an abundance of supporting data. As always, the Report incorporates research from all over the world, analyzing the conditions that surround the growth process and offering insights on appropriate policy measures for the future.
Each issue has also a distinctive title.
Includes bibliographical references.
oif 31/01/2019
Ref.
Keywords: Economic development; Developing countries